Investigation of a Metallic Interconnect Extracted from an SOFC Stack after 40,000 h of Operation - Paolo Piccardo; Roberto Spotorno; Christian Geipel (Energies, 2022)
An in-depth investigation was performed on a metallic interconnect extracted from an SOFC stack operated for 40,000 h. The characterization was performed on the surface and the cross-section, paying attention to the evolution of the materials due to the interaction with the dual atmosphere of the stack under operating parameters. The interaction between materials (i.e., metal substrate, coatings and atmospheres) and stack components (i.e., current collectors and MIC) generated several modifications that affected the surface and, in some cases, the bulk of the interconnect. The careful metallographic preparation allowed for the performance of an intensive microscopical characterization of the cross-sections all along the interconnect profile, from the inlet to the outlet of the fuel stream. The formation of thermal grown oxides on both sides and their evolution were studied and described. The interconnect, after 40,000 h, was still suitable for operation, but the few bulk changes due to the diffusion of Ni and the TGO that formed at the fuel side suggest the introduction of fuel side coatings to increase the life expectations of the whole stack.